Economic Performance of Indonesian Manuffacturing Ccompanies With Factors - Dirvi Surya Abbas; Arry Eksandy; Mulyadi (International Journal of Science, Technology & Management, 2020)
purpose of this research is to determine the effect of Enterprise Risk Management (ERM), Inventory Intensity, Corporate Image and Intangible Asset to Economic Performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 4-year period 2015-2018. This study population includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 17 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is linear regression analysis of panel data.The results showed that Inventory Intensity and Corporate had a significant effect on Economic Performance. while Enterprise Risk Management and Intangible Asset has no effect on intellectual capital.